Risk Factors Affecting Length of Stay in Preterm Infants at Wangaya Regional General Hospital, Indonesia - Putri Prashanti, Nyoman Ananda; Kanthi Soraca Widiatmika; Putu Siska Suryaningsih; I Wayan Bikin Suryawan (HM Publisher, 2024)
Background: Advances in neonatology have led to many preterm infants being saved. Prolonged length of stay (LOS) increases the incidence of neonatal complications and even mortality, placing a significant economic burden on families and strain on healthcare systems. This study aims to determine the factors associated with LOS in preterm infants. Methods: This cross-sectional study involved 60 preterm babies treated at Wangaya Hospital from May 2022 to May 2023. Infants with congenital anomalies, referred from other hospitals and did not receive appropriate treatment were excluded from the study. Data were taken from the electronic medical record after obtaining ethical clearance and then analyzed using descriptive statistics and linear regression in SPSS 25. Statistical significance was considered at 0.05. Results: As many as 46 out of 60 preterm infants were born at moderate to late preterm gestational age. The majority of 81.7% of infants were born with a body weight of 1500-2499 grams. The median number of LOS was 7.5 days (IQR 15). Multivariate analysis of numerical independent variables obtained an equation log [LOS] = 2.902-0.066*gestational age+ 0.022*duration of parenteral nutrition (R2 = 78.1%). Meanwhile, in the categorical independent variables obtained, an equation log [LOS] = 0.398 + 0.223*very preterm + 0.144* RDS + 0.178*NEC + 0.206*prolonged antibiotics administration + 0.278*late enteral feeding + 0.148*abdominal distension + 0.144*vomiting (R2 = 87.4%). Conclusion: Factors influencing LOS of preterm infants are gestational age, duration of parenteral nutrition, the presence of RDS, NEC, vomiting, abdominal distension, late enteral feeding, and prolonged use of antibiotics. It is essential to carry out antenatal care for pregnant women to prevent premature birth.